(untitled) (International Journal of Engineering and Computer Science, 2016)
The primary use of cloud computing is information storage. Cloud provides enormous capability of storage for cloud users. It is lot of reliable and versatile to users to store and retrieve their information at anytime and anyplace. It is an progressively growing technology. Nowadays, several enterprises have started using cloud storage because of its benefits. Even though the cloud continues to gain popularity in usability and attraction, the issues belong information security, data privacy and alternative data protection problems. Security and privacy of information stored in the cloud are major setbacks within the field of Cloud Computing. Security and privacy of the information stored in cloud are the key issues. This paper offers the brief discussion on cloud data security.